Systems and Electronic Data Processing Courses in the Accounting Curriculum. - Schroeder, Joan Gagnon (The Accounting Review, 1972)
The article presents information on accounting curriculum in the U.S. In 1969 the American Institute of Certified Public Accountants Committee (AICPA) on Education and Experience Requirements for Certified Public Accountant recommended four-semester hours of computers and information systems in business, preceded by a two to three-hour course, introduction to the computer, as part of a model program for a four-year undergraduate degree in accounting. The five-year preferred program would increase the systems component to six hours. These specific recommendations followed similar suggestions made over the years by various committees of both the American Accounting Association and the AICPA. Rapid developments in the areas of systems and electronic data processing and their identification with accounting information processing and analysis demand that, beginning accountants have a firm understanding of the basic concepts, principles and uses involved. The rate of implementation of required courses in EDP and in systems must be accelerated if these needs are to be satisfied. Twenty-eight schools required one of the courses and had the second available as an elective.